Efficacy and safety of PARP inhibitors monotherapy or combination therapy with anti-angiogenics in ovarian cancer: a network meta-analysis - Liu, Yuan; Ren, Tongtong; Wang, Xinchun; Wang, Yuqi; Tang, Lisha; Cao, Wenjiang (Frontiers in Oncology, 2026)
BackgroundThe incidence of ovarian cancer ranks second only to cervical cancer and uterine cancer, but its mortality rate is the highest. Searching for effective and safe PARP inhibitors - antiangiogenic drugs combined treatment for ovarian cancer is a new approach.MethodConducted a comprehensive search in the authoritative databases, with the search period ranging from the establishment of these databases until December 2024. And conducted a Bayesian network meta-analysis using R 4.3.1 and Stata 16.0.The primary endpoint was progression-free survival (PFS), and the secondary endpoint was adverse events (AEs) (≥grade 3).ResultsThe analysis ultimately incorporated 15 RCTs from 18 publications, involving 6,416 patients and evaluating nine distinct treatment regimens. All PARPi monotherapies and combination therapies demonstrated significant PFS improvement versus placebo (P ≤ 0.05). Compared with niraparib alone(HR = 2.85; 95%CI:1.2-6.79), niraparib+bevacizumab showed significant difference in improving PFS in ovarian cancer patients (P ≤ 0.05). olaparib+cediranib had significant difference in improving PFS compared with olaparib(HR = 1.36; 95%CI:1.06-2.26) (P ≤ 0.05). Besides, niraparib+bevacizumab ranked first in improving PFS, followed by olaparib+ cediranib. In terms of safety, there was no statistically significant difference in AEs (grade≥3) between different PARP inhibitors or in combination with antiangiogenic agents for ovarian cancer.ConclusionCurrent evidence indicates that the combination of PARPi and anti-angiogenic drugs in the treatment of ovarian cancer is superior to PARPi monotherapy. Niraparib combined with bevacizumab may show the most optimal effect in improving PFS, and it might be a better combined treatment option. In monotherapy, senaparib has shown good efficacy. The incidence of AEs of various PARPi is similar, but the incidence of adverse reactions is relatively high when used in combination mode. A reasonable treatment plan should be selected based on the individual conditions of patients.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD 420251003413.